Guidelines and standards for the study of death and recalled experiences of death––a multidisciplinary consensus statement and proposed future directions. Issue 1 (18th February 2022) - Parnia, Sam; Post, Stephen G.; Lee, Matthew T.; Lyubomirsky, Sonja; Aufderheide, Tom P.; Deakin, Charles D.; Greyson, Bruce; Long, Jeffrey; Gonzales, Anelly M.; Huppert, Elise L.; Dickinson, Analise; Mayer, Stephan; et al.
Abstract: An inadvertent consequence of advances in stem cell research, neuroscience, and resuscitation science has been to enable scientific insights regarding what happens to the human brain in relation to death. The scientific exploration of death is in large part possible due to the recognition that brain cells are more resilient to the effects of anoxia than assumed. Hence, brain cells become irreversibly damaged and "die" over hours to days postmortem. Resuscitation science has enabled life to be restored to millions of people after their hearts had stopped. These survivors have described a unique set of recollections in relation to death that appear universal. We review the literature, with a focus on death, the recalled experiences in relation to cardiac arrest, post–intensive care syndrome, and related phenomena that provide insights into potential mechanisms, ethical implications, and methodologic considerations for systematic investigation. We also identify issues and controversies related to the study of consciousness and the recalled experience of cardiac arrest and death in subjects who have been in a coma, with a view to standardize and facilitate future research. Abstract : We review the literature, with a focus on death, the recalled experiences in relation to cardiac arrest, post–intensive care syndrome (PICS), and related phenomena that provide insights into potential mechanisms, ethical implications, and methodologic considerations for systematic investigation. We also identify issues and controversies related to the study of consciousness and the recalled experience of cardiac arrest and death in subjects who have been in a coma, with a view to standardize and facilitate future research.